Effectiveness and Safety of Extubation before Reversal of Neuromuscular Blockade versus Traditional Technique in Providing Smooth Extubation - Babu, Karthik C; Rajan, Sunil; Sandhya, Sai V K; Raj, Renjima; Paul, Jerry; Kumar, Lakshmi (Anesthesia, essays and researches, 2021)
Traditional extubation often leads to bucking, coughing, and undesirable hemodynamic changes. Extubation just before administering reversal could reduce force of coughing, bucking and may provide better extubation conditions. The aim of the study was to assess the incidence of bucking with extubation just before administering reversal of neuromuscular blockade compared to traditional technique of awake extubation. Incidence of coughing during extubation, vomiting/regurgitation, aspiration, hemodynamic changes, postoperative bleeding, and extubation conditions were also assessed. This was a prospective randomized study conducted in a tertiary care institute. Forty patients were allocated into two equal groups. In Group E, at the end of surgery, extubation was performed and reversal was administered after extubation. In Group L, reversal was given and patients were extubated in the traditional way. Quality of extubation was assessed using extubation quality score. Pearson Chi-square test, Fisher's exact test, and independent sample -test. Group E showed significantly lower incidence of bucking (15% vs. 65%) and coughing (10% vs. 45%). Incidences of desaturation and regurgitation/aspiration were comparable. In Group E, 85% of patients did not cough during extubation compared to 50% in Group L. Extubation quality was significantly better in Group E. Although extubation time was significantly shorter in Group E, recovery time was comparable in both groups. Extubation just before reversal of neuromuscular blockade resulted in lesser incidence of bucking and coughing during extubation with lesser postoperative bleeding compared to traditional technique of awake extubation without added risks of regurgitation, aspiration, or delayed recovery.